Analysis of performance of classification of Forward-Scattering Radar (FSR) in a cluttered environment / Muhammad Najmi Afiq Yahya - Yahya, Muhammad Najmi Afiq (2014)
This thesis presents the analysis result of clutter to the radar data dispersion. The presence of chutter from enviroment may cause error in the target detection and classification in forward scattering radar (FSR).